Comparison of Two Home-based Chemically-induced Teeth Whitening in Adults: A Randomised Clinical Trial - Santos, Jose Sebastiao Galvao dos; Silva, Kamilla Yolanda de Souza e; Felix, Larissa Hellen de Paiva; Dias, Marlon Ferreira [UNESP]; Lins Filho, Paulo Cardoso; Silva, Claudio Heliomar Vicente da; Guimaraes, Renata Pedrosa (Premchand Shantidevi Research Foundation, 2022)
Introduction: Whitening strips are one of the Over The Counter (OTC) bleaching products which performed tooth whitening through an easy-to-use, low-cost product with good esthetic results. Aim: To compare the bleaching efficacy, tooth sensitivity and gingival irritation, and of home-based chemically-induced teeth whitening treatment performed using either a conventional customised tray or strips as delivering systems for whitening agents. Materials and Methods: This randomised clinical trial was conducted at Federal University of Pernambuco (UFPE), Brazil, from 15th May 2015 to 20th January 2018. Total 21 subjects, with maxillary incisor's shade A3 or darker were selected for this study. Patients were randomly assigned into two groups, according to the bleaching technique used i.e, G1 (n=10) was carbamide peroxide 10% (Whiteness Perfect/FGM) delivered in a customised tray, G2 (n=10) was hydrogen peroxide 10% delivered in strips (3D White Whitestrips/OralB). Color changes were evaluated by an objective (Easyshade Spectrophotometer/ VITA) method at baseline, middle of treatment period, end of treatment, 15 and 30 days after treatment end. Tooth sensitivity, gingival irritation and degree of satisfaction were also recorded. Fisher's-exact test was used for categorical variables i.e, Kolmogorov-Smirnov Normality Test for quantitative variables and Mann-Whitney's test for comparison between two groups. Results: No significant difference was observed in occurrence of tooth sensitivity (p-value=0.635), gingival irritation (p-value=0.090) and treatment satisfaction (p-value=0.476) between groups. Increased whitening effectiveness was observed in both groups after 30 days of clinical evaluation, however with no significant difference between groups (p-value=0.139). Conclusion: Both bleaching systems showed similar effectiveness and high degree of satisfaction. Low degree of tooth sensitivity and gingival irritation was observed with no difference between groups.
Keywords: Clinical trial; Dentin sensitivity; Peroxides; Tooth bleaching; Tooth bleaching agents